Effect of Lesser Yam Flour Addition on Water Content, Texture, Crude Fiber Content, and Reducing Sugar Content of Donut Made from Wheat Flour - Indri Iriana Putri; Bambang Dwiloka; Valentinus Priyo Bintoro (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2020)
This research aimed to determine the addition of lesser yam flour on water content, texture, crude fiber content, and reducing sugar content of donut made from wheat flour. This research was arranged using completely randomized design with 5 treatments and 4 replications consisted of 5 different lesser yam flour concentrations (0–30%) from total flour that had been used. Water content, texture, and crude fiber content were analyzed using Analysis of Variance (ANOVA) at 5% significance level and reducing sugar content was analyzed using regression equation. The result showed the addition of lesser yam flour can reduce water content. However, it can increase texture, crude fiber content, and reducing sugar content. As conclusion, the concentration of lesser yam flour affected the water content, texture, crude fiber, and reducing sugar in donut.